Projecting climate-driven shifts in demersal fish thermal habitat in Iceland's waters. (16th November 2021) - Mason, Julia G; Woods, Pamela J; Thorlacius, Magnús; Guðnason, Kristinn; Saba, Vincent S; Sullivan, Patrick J; Kleisner, Kristin M
Abstract: As climate change shifts marine species distribution and abundance worldwide, projecting local changes over decadal scales may be an adaptive strategy for managers and industry. In Iceland, one of the top fish-producing nations globally, long-term monitoring enables model simulations of groundfish species habitat distribution. We used generalized additive models to characterize suitable thermal habitat for 51 fish species in Iceland's waters. We projected changes in suitable thermal habitat by midcentury with an ensemble of five general circulation models from the Coupled Model Intercomparison Program 6 (CMIP6) and NOAA (CM2.6) and two scenarios (SSP 5-8.5 and SSP 2-4.5). We found a general northward shift in suitable thermal habitat distribution, with variable regional dynamics among species. Species thermal bias index was a weak predictor of projected thermal habitat change, with warmer-water species more likely to see increases in thermal habitat and southern warm-edge range expansions. While these results isolate the effects of future changes in temperature, providing an indication of suitable thermal habitat, low model explanatory power suggests that additional variables may improve distribution projections. Such projections might serve as guideposts to inform long-term management decisions about regional and species-specific suitability for Iceland's fisheries, infrastructure investment, and risk evaluation under climate change.